Hinduism : a very short introduction - Knott, Kim (Very short introductions., 1998)
"Hinduism is practised by eighty per cent of India's population, and by thirty million people outside India. In this Very Short Introduction, Kim Knott combines a succinct and authoritative overview of a major religion with an analysis of the challenges facing it in the twentieth century. She discusses key preoccupations of Hinduism such as the centrality of the Veda as religious texts, the role of brahmins, gurus, and storytellers in the transmission of divine truths, and the importance of epics such as the Ramayana. Issues such as the place of women and dalits (untouchables) in contemporary society are also addressed, making this book stimulating reading for Hindus and non-Hindus alike."--EBSCO